Perancangan Sistem Pelaporan Kecelakaan Lalu Lintas Menggunakan Metode Agile Guna Menunjang Rekam Medis Elektronik - Irwansyah, Deden Rian; M., Imas Dian; Syahidin, Yuda; Taufik, Rizal (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2023)
Based on research findings conducted at X Hospital, the problem of reporting traffic accidents is done manually and using Microsoft Excel. As a result, the process of reporting traffic accident data can take a long time because officers need to enter data into Microsoft Excel one by one. This study collects data by observation, interviews, and literature study. Integrated system design is the goal of this research. An agile approach is used in designing the traffic accident reporting system. The application is developed using Microsoft Access database and visual programming language, and the system is tested using black-box testing. The results of this design are able to streamline the performance of medical record officers in making fast and accurate reporting.